Development of Unit Price Contract Standards Between Main Contractor and Subcontractor in PT XYZ Factory Home Appliance Project Based on Contract Management Body of Knowledge to Reduce Claims on Project - Anggraini, Rika; Latief, Yusuf; Riantini, Leni Sagita (AIBPM Publisher, 2023)
Contract management methods are important in a construction project. The factory home Appliance project is one of the national strategic projects in an industrial area. In the execution of the contract, there are claims that occur between the main contractor and the subcontractor. This research was conducted to provide the development of contract management based on Contract Management Body of Knowledge to reduce risk-based claims. The results of this study can provide input and new guidelines for contract management that will be carried out in the future.